2004
DOI: 10.1002/bdra.20103
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the ADH1C polymorphism and maternal alcohol intake in the risk of nonsyndromic oral clefts: An evaluation of the contribution of child and maternal genotypes

Abstract: Because the ADH1C gene is involved in the metabolic pathways of many alcohols, we propose several hypotheses about the causal pathway, including ethanol oxidation activity and, more probably, retinol oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 42 publications
0
34
0
4
Order By: Relevance
“…Analyses excluding them produced similar conclusions. We have previously discussed in detail the recruitment, data collection and environmental exposure assessment strategies for this case-control study [Chevrier et al, 2005[Chevrier et al, , 2006[Chevrier et al, , 2007a. Maternal smoking during the first trimester of pregnancy was not associated with the risk of nonsyndromic oral cleft in this population.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Analyses excluding them produced similar conclusions. We have previously discussed in detail the recruitment, data collection and environmental exposure assessment strategies for this case-control study [Chevrier et al, 2005[Chevrier et al, , 2006[Chevrier et al, , 2007a. Maternal smoking during the first trimester of pregnancy was not associated with the risk of nonsyndromic oral cleft in this population.…”
Section: Discussionmentioning
confidence: 97%
“…The allele-specific oligonucleotide method, described in a previous report [Chevrier et al, 2005], was used for five polymorphisms: the TGFA TaqI polymorphism-a substitution of an insertion/deletion of four bp (called C2) [Qian et al, 1993], the TGFB3 T-24in4C (the C allele labeled X5.1), the MSX1 T2090G (included in the N8 haplotype described elsewhere [Mitchell et al, 2001]), CYP1A1 I462V resulting from an A to G substitution at position þ131 of intron7, and CYP1A1 þ1189, from a T to C substitution at 3' of the gene. These latter two polymorphisms are noted, respectively, as CYP1A1*2A and CYP1A1*2C [Human Cytochrome P450 Allele Nomenclature Committee].…”
Section: Assessment Of Maternal Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…24 These compounds are metabolized by alcohol dehydrogenase, 25 and possession of the slow-metabolizing variant of the alcohol dehydrogenase 1C (ADH1C) gene by either mother or fetus has been shown to increase the fetus's vulnerability to alcohol-related oral clefts. 26,27 TCOH and TCAA are the principal metabolites of tetrachloroethylene and trichloroethylene, present in a variety of compounds common in occupational use. Several animal studies report adverse developmental effects of trichloroethylene or TCAA, mainly cardiac malformations 28 or delayed ossification in rat whole-embryo culture.…”
Section: Discussionmentioning
confidence: 99%
“…25 Recently, it was suggested the Ile350Val variant at ADH1C may protect against oral clefts, but there was no significant evidence for an effect of fetal genotype or interaction with maternal alcohol consumption. 26 The gamma 2 protein (corresponding to the 272Gln-350Val haplotype) results in slower ethanol oxidisation than the gamma 1 protein (272Arg-350Ile haplotype). 27 Our study showed significant over-transmission of the A allele at rs1693482 (which results in a Gln at amino acid 272) to affected children compared to the frequencies of A allele among mothers and fathers (0.44 v 0.41 and 0.38, respectively; p = 0.008).…”
Section: Discussionmentioning
confidence: 99%